The Effect of Profitability and Liquidity on The Stock Returns at PT. Kimia Farma Tbk - Nugraha Hidayat, Gildan; Hernawati, Euis (International Research & Development for Human Beings (IRDH), 2024)
This study seeks to examine the influence of profitability and liquidity on stock returns in PT. The study method utilized is a quantitative approach, specifically employing multiple linear regression analysis. To The stock return variable is calculated by determining the difference between the current year's stock price and the previous year's stock price, thereafter dividing this difference by the prior year's yearly price. The profitability variable is assessed using ROA, while the liquidity variable is evaluated using CR. This research was conducted on PT. Kimia Farma Tbk, utilizing the yearly financial reports from the IDX for the period 2019-2023. The study's findings demonstrated that neither profitability nor liquidity characteristics significantly influenced stock returns. And simultaneously the profitability and liquidity variables do not significantly affect stock returns, as their significance values are negligible. Consequently, variations in profitability and liquidity quality do not influence the company's stock return rate.